LEGAL CONSEQUENCES OF VIOLATION OF A CHILD SUPPORT AGREEMENT - Veres, Iryna (Socio-economic relations in the digital society, 2024)
The article offers a comprehensive approach to determining the legal consequences of violating the child support agreement. Termination of the contract is a necessary condition for the exercise of the right to apply to the court with a statement or claim for the collection of alimony and additional expenses. Therefore, it is expedient for the SC of Ukraine to provide for the right to unilaterally withdraw from the contract in the event of a delay in the performance of the obligation, to define in the contract the meaning of the concept of "substantial breach of contract - delay within a certain period of time", which may be grounds for terminating the contract.The Civil Code of Ukraine provides for the right to collect a penalty (penalty) only if the arrears arise due to the fault of the person who is obliged to pay alimony. The principle of "the best interests of the child" dictates the need to extend these provisions to cases of late payment of additional expenses for the child. It is also important to provide a penalty for late fulfillment of the obligation to maintain in kind. Before making the appropriate additions to the SC of Ukraine, it is advisable to provide a penalty clause in the contract. In order to improve the legal regulation, it is necessary to provide a condition for the application of the general rule for determining the amount of the penalty in accordance with Part 1 of Art. 196 of the Civil Code of Ukraine, unless otherwise stipulated by the contract.The child may also have the right to compensation for damages and (or) moral damage. In order to avoid future disputes, it is advisable in the contract to provide for the obligation to compensate moral damages in the event of a delay in the maintenance obligation and the amount of compensation for moral damages.
Keywords: maintenance; alimony; additional expenses for the child; agreement on child maintenance; penalty; interest; damages; moral damage